Culturally sensitive patient-centered healthcare: a focus on health behavior modification in low and middle-income nations—insights from Indonesia - Cipta, D. A; Andoko, D.; Theja, A.; Utama, A. V. E.; Hendrik, H.; William, D. G.; Reina, N.; Handoko, M. T.; Lumbuun, N. (Frontiers in Medicine, 2024)
Patient-centered, culturally sensitive healthcare acknowledges the impact of cultural beliefs on health behaviors and outcomes, particularly vital in low and middle-income countries (LMICs). Within Indonesia, distinct cultural factors are pivotal in empowering patients, necessitating their integration into healthcare practices. For example, the cultural concept of gotong royong, emphasizing communal collaboration, presents an opportunity to foster community support networks among patients. Acknowledging and incorporating spiritual and religious beliefs, which are deeply rooted in Indonesian culture, into healthcare interventions further augments patient empowerment and well-being. In LMICs, including Indonesia, achieving patient empowerment demands implementing critical strategies. Community-based interventions harness local resources and engage the community to drive health behavior change. Culturally sensitive communication bridges the gap between healthcare providers and patients. Patient education fosters a comprehensive understanding of health conditions, thereby encouraging active involvement in decision-making. This review emphasizes the pivotal role of patient-centered, culturally sensitive healthcare in LMICs, particularly in Indonesia. It delves into strategies to promote health behavior change within these unique contexts, emphasizing the importance of cultural sensitivity and patient-centered care. The discourse also explores the cultural landscape impacting healthcare, acknowledging the challenges faced in delivering comprehensive healthcare services within these diverse cultural contexts. Additionally, it outlines innovative approaches and success stories in implementing patient-centered care, highlighting how cultural factors intersect with healthcare outcomes. By advocating for integrating culture-specific patient empowerment practices into healthcare methodologies, this article underscores the potential for improved health outcomes, heightened patient engagement, and the delivery of culturally relevant services within LMICs.